2011
DOI: 10.3136/fstr.17.515
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Cyanidin and Cyanidin-3-glucoside on Human Cell Lines

Abstract: Anthocyanins are pigments in plants. Anthocyanins and their aglycons, anthocyanidins, have various biological effects. In the present study, we examined the effects of cyanidin and cyanidin-3-glucoside on intracellular reactive oxygen species (ROS) levels and on proliferative effects, using four cancer cell lines and one normal cell line, and we found that cyanidin (100 μmol/L) has significant effects when compared with cyanidin-3-glucoside. Cyanidin reduced intracellular ROS levels in MCF-7, HuH-7, HepG2, Cac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…The obtained results show that: 1) The small differences in the spectral structures (CGA and CG) may significantly alter the ROS inhibition of cyanidin 3- O -glycosides; 2) the presence of monosaccharide at C 3 (CA, CGA, CG) does not change the inhibitory activity in comparison to aglycone (C), but the presence of disaccharides (CR) inhibits it significantly; and 3) the presence of an additional sugar group at C 5 (CDG) does not change the inhibition of ROS generation determined for 3- O -glycosides of cyanidin. Contrary to our results, Takeuchi et al [25] indicated that C decreased the intracellular ROS levels of different cell lines (MCF-7, HuH-7, HepG2, Caco-2, and HUVEC), but its O -glycosides (CG) did not, and therefore they postulated that these differences are not cell specific. On the other hand, similar to our results, decreased intracellular ROS levels under the influence of O -glycosides of cyanidin were observed, e.g., for human HaCaT keratinocytes and HUVEC cells [38,39].…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The obtained results show that: 1) The small differences in the spectral structures (CGA and CG) may significantly alter the ROS inhibition of cyanidin 3- O -glycosides; 2) the presence of monosaccharide at C 3 (CA, CGA, CG) does not change the inhibitory activity in comparison to aglycone (C), but the presence of disaccharides (CR) inhibits it significantly; and 3) the presence of an additional sugar group at C 5 (CDG) does not change the inhibition of ROS generation determined for 3- O -glycosides of cyanidin. Contrary to our results, Takeuchi et al [25] indicated that C decreased the intracellular ROS levels of different cell lines (MCF-7, HuH-7, HepG2, Caco-2, and HUVEC), but its O -glycosides (CG) did not, and therefore they postulated that these differences are not cell specific. On the other hand, similar to our results, decreased intracellular ROS levels under the influence of O -glycosides of cyanidin were observed, e.g., for human HaCaT keratinocytes and HUVEC cells [38,39].…”
Section: Resultscontrasting
confidence: 99%
“…Aglycone (cyanidin) inhibited lipopolysaccaride-induced cyclooxygenase 2 (COX-2) expression [23], influenced the function of endothelial cells, and exerted an inhibitory effect on oxidative injury of the cells [24]. Cyanidin also reduced intracellular ROS (reactive oxygen species) levels in the MCF-7, HuH-7, HepG2, Caco2, and HUVEC cell lines and inhibited the proliferation of cancer cells [25]. Cyanidin-3- O -rutinoside induced the accumulation of peroxides, which are involved in the induction of apoptosis in HL-60 cells [26] and may suppress the inflammatory response via inhibition of NO and PGE2 release and modulation of gene expression [27].…”
Section: Introductionmentioning
confidence: 99%
“…Such findings might be related to differences in anthocyanin profiles in the FW digests, particularly the approximately two-fold greater content of the aglycone cyanidin and petunidin anthocyanins in the Leona versus Amachi colonic reactors. Cyanidin, but not its glycosides, was shown to be a potent inhibitor of the growth of human colon carcinoma HT-29 cells [ 55 ] or HCT-116 [ 56 ] and Caco-2 [ 57 ] colon cancer cells. Aglycones such as cyanidin can readily be released following intestinal microbial beta-glucosidase-mediated hydrolysis of anthocyanins [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it seems that different anthocyanins vary in their bioactivity. Several studies have investigated this aspect toward the antioxidative potential of anthocyanins , but not much is known about the impact of different anthocyanidins and the degree of glycosylation on the anti‐inflammatory potential of anthocyanins. Nonetheless, one in vitro study investigated the influence of different anthocyanidins on COX‐2 expression.…”
Section: Discussionmentioning
confidence: 99%